Annemarie Schwarzenbach’s "The Happy Valley": translation changed narrator’s gender – ma non troppo - Cuartero Otal, Juan (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
It is an obvious fact that Literary Criticism always offers an effective aid to the translation of literary texts. But what happens if theoretical studies do not agree on a characteristic that seriously conditions the translation of a work? This is the case with the novel Das glückliche Tal by the Swiss writer Annemarie Schwarzenbach, since scholars do not agree on the genre of its narrator. In this paper, the translator of that novel into Spanish justifies his approach to the text and his decisions.